English Learning Media at SMP Negeri 8 Palopo - Sri Damayanti; Irwan Irwan (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
This paper describes the performance and the weaknesses of the English learning media created by student of English Education Study Program and applied at SMP Negeri 8 Palopo. This English learning media can improve the students’ vocabulary and the teacher and students of SMP Negeri 8 Palopo give positive response toward this English learning media but still there are many suggestions to the author. After analysing this media, it is found that the performance of this media have weaknesses such as: the material, exercise, pronunciation, and picture.